Novel Federated Decision Making for Distribution of Anti-SARS-CoV-2 Monoclonal Antibody to Eligible High-Risk Patients - Jameel Rabee Jameel Al-Obaidi, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan (Tanjung Malim, 2024)
Novel Federated Decision Making for Distribution of Anti-SARS-CoV-2 Monoclonal Antibody to Eligible High-Risk Patients by Jameel Rabee Jameel Al-Obaidi, Abdullah Hussein Abdullah Al-Amoodi, Salem Abdullah Salem Garfan